2013
DOI: 10.1152/ajpcell.00043.2013
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine response of primary human myotubes in an in vitro exercise model

Abstract: Muscle contraction during exercise is a major stimulus for the release of peptides and proteins (myokines) that are supposed to take part in the beneficial adaptation to exercise. We hypothesize that application of an in vitro exercise stimulus as electric pulse stimulation (EPS) to human myotubes enables the investigation of the molecular response to exercise in a clearly defined model. We applied EPS for 24 h to primary human myotubes and studied the whole genome-wide transcriptional response as well as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
119
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(127 citation statements)
references
References 47 publications
5
119
2
1
Order By: Relevance
“…This may reflect an inherent abnormal IL-6 response in insulin-resistant skeletal muscle (27,47). It has previously been shown that EPS increased gene expression of IL-8 in lean nondiabetic myotubes (48), and our current data indicate that the impact of EPS on gene expression of IL-8 differs in myotubes from severely obese nondiabetic subjects compared with diabetic subjects. Exercise-derived IL-8 is postulated to stimulate angiogenesis in skeletal muscles (39), but the biological role of muscle-derived IL-8 remains to be clarified.…”
Section: Ajp-cell Physiolsupporting
confidence: 48%
See 2 more Smart Citations
“…This may reflect an inherent abnormal IL-6 response in insulin-resistant skeletal muscle (27,47). It has previously been shown that EPS increased gene expression of IL-8 in lean nondiabetic myotubes (48), and our current data indicate that the impact of EPS on gene expression of IL-8 differs in myotubes from severely obese nondiabetic subjects compared with diabetic subjects. Exercise-derived IL-8 is postulated to stimulate angiogenesis in skeletal muscles (39), but the biological role of muscle-derived IL-8 remains to be clarified.…”
Section: Ajp-cell Physiolsupporting
confidence: 48%
“…Gene regulation involved in exercise adaptation is complex (14,48), but genes regulated by PPAR␦ may be involved (15). It has also been proposed that PPAR␦ agonists and exercise training synergistically increase the proportion of type 1 fibers (MHCI) in adult mice (35).…”
Section: Ajp-cell Physiolmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, IL-6, CCL2, and CXCL1 rise in the circulation during exercise (5,22), but the cellular source is unknown. These cytokines are also secreted from contracted mouse C 2 C 12 myotubes (8,22) and cultured primary human myotubes (32,36,37), suggesting the possibility that muscle cells may be a direct source of circulating chemoattractants in response to exercise. As Pedersen and Febbraio proposed, "myokines" (defined as cytokines and other peptides that are produced and released by muscle fibers) may exert autocrine, paracrine, or endocrine effects (28).…”
mentioning
confidence: 99%
“…1 hour, 3 hours and up to 24 hours), which in line with my main aim was employed to identify the transcriptional events that precede the induction of inflammation under the activation of adenosine A2B receptors. It has shown previously 57 that most of the inflammatory transcripts studied (such as IL-6) in skeletal muscle cells are not translated into protein within that time frame. Therefore my future studies using longer durations of NECA (after 24 hours) will be recommended to investigate the translational changes in response to treatment.…”
Section: Discussionmentioning
confidence: 99%